Evaluasi Program Ekstrakulikuler di Pondok Pesantren Al-khoir Padang Lawas Sumatera Utara - Nurhasanah Harahap; Fahmi Rizal (Universitas Negeri Padang, 2020)
Abstract- Extracurricular program is a learning process in which performed outside of school. The study attempts to explore the components of context, input, process and product of extracurricular program at Al-Khoir Islamic boarding school. In this study, the evaluation model used by Stufflebeam namely the CIPP (context, input, process, product) evaluation model. This study used mixed method; qualitative and quantitative. interviewing was carried out with the teacher (qualitatively) while scoring students’ test result (quantitatively). The findings showed that the components of context, input, process, product and results of extracurricular program at Al-Khoir Islamic boarding school were categorized as good. Therefore, Al-Khoir boarding school could maintain the extracurricular program and continue to improve any perceived shortcomings after evaluating the program. Thus, in this study, students are suggested to be more active and serious in extracurricular programs because it is very useful for them to add their knowledge and skills. It is suggested to make the improvements to each component of the context, input, process and product and to be more active and innovative in designing curriculum and planning before doing the extracurricular programs. Keywords : Mixed Method, CIPP, Extracurricular Program